2013
DOI: 10.3390/v5123071
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeographic Diversity of Pathogenic and Non-Pathogenic Hantaviruses in Slovenia

Abstract: Slovenia is a very diverse country from a natural geography point of view, with many different habitats within a relatively small area, in addition to major geological and climatic differences. It is therefore not surprising that several small mammal species have been confirmed to harbour hantaviruses: A. flavicollis (Dobrava virus), A. agrarius (Dobrava virus–Kurkino), M. glareolus (Puumala virus), S. areanus (Seewis virus), M. agrestis, M. arvalis and M. subterraneus (Tula virus). Three of the viruses, namel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 32 publications
3
17
0
Order By: Relevance
“…If RVB is not a primary pathogen, evolutionary pressures from the host immune system may facilitate unrestricted evolution into novel genotypes. Non-pathogenic hantaviruses [ 31 ] and Fusarium oxysporum [ 32 , 33 ] have higher genetic diversity when compared to their pathogenic relatives, which supports the hypothesis of RVB as a secondary pathogen.…”
Section: Discussionsupporting
confidence: 53%
“…If RVB is not a primary pathogen, evolutionary pressures from the host immune system may facilitate unrestricted evolution into novel genotypes. Non-pathogenic hantaviruses [ 31 ] and Fusarium oxysporum [ 32 , 33 ] have higher genetic diversity when compared to their pathogenic relatives, which supports the hypothesis of RVB as a secondary pathogen.…”
Section: Discussionsupporting
confidence: 53%
“…Given the strong geographic association within > 90% of our hantavirus sequences and the close phylogenetic relationship between human and rodent derived sequences from the same area [15-17,42], there are strong indications that human infections commonly occur close to the cases homes. The few discrepancies observed between phylogenetic cluster and the respective geographic location can be explained by the daily commute or travel history as reported by the case or are compatible with short (day) leisure trips.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies have indicated that SWSV is widespread throughout Europe and Asia across the vast distribution of its soricid reservoir, in Austria, Czech Republic, Finland, Germany, Hungary, Russia, Slovakia and Slovenia (Kang et al, 2009a; Klempa et al, 2013; Korva et al, 2013; Resman et al, 2013; Schlegel et al, 2012b). SWSV has also been detected in the Siberian large-toothed shrew ( S. daphaenodon ) and tundra shrew ( S. tundrensis ) in Russia (Yashina et al, 2010).…”
Section: Introductionmentioning
confidence: 99%